LE BESOIN D’EXCEPTIONS NÉGATIVES DANS LES PAYS GOUVERNÉS PAR LA NORME - Jean-Jacques SARFATI (Studia Universitatis Babeș-Bolyai. Philosophia, 2016)
The Inconscient Need of Exception in All the Countries where Standards are Gouverning. How can we explain the current legal situation in France in this moment? This country opted for the state of emergency which question several part of its legal human rights. Of course, the tragic situation which knows this country -and with him all western Europe- is at the origin of this cruel situation. However, here, the Author proposes another explanation which naturally not exclude the others. France and with her all the occidental world - opted for legal normativisme. This normativisme highlight the idea of laws, principles and norms and ignores the notion of exception. This term was effectively studied by C. Schmitt but this author proposed a too reduced and dogmatic approach. This approach as influenced Europe but it’s not what we need for law. The Author proposes here a more open signification of the term and a positive sens for him (for example: moments of big national and international enjoyment). In other words for him, if you give to people more joy and exceptional happiness, it will not the "inconscientious" desire of tragic exception. When one excludes exception of law, it comes back, but not in her "good" and pleasant sense.